Determining the association between oral health status and self-perceived oral health satisfaction among residents in the largest care home in East Coast Malaysia - Mohd, Farah Natashah; Said, Abdul Hadi; Yusof, Muhammad Zubir; Ismail, Nor Iziana; Musa, Nor Mulyani (2019)
Introduction: Little is known about the association between actual and selfperceived oral health status among residents living in a care home. This study aimed to assess their oral health status and to determine its association with their selfperceived oral health satisfaction. Materials and method: A cross-sectional study was conducted from July to August 2018 among 75 residents of Rumah Ehsan, Terengganu (the largest care home in east coast Malaysia). The oral health status and oral hygiene of the participants were examined. Their sociodemographic profile and self-perceived oral health status were collected through structured interviews. Chi-square, Man-Whitney, and multiple logistic regression tests were used to test the factors associated with the self-perceived oral health satisfaction of the participants. Results: Unsurprisingly, the majority of the participants had poor oral health with high median DMF-T score of 29.0 (IQR =12) and majority (86.7%) had poor oral hygiene. It was intriguing to know that the majority of them (64%) perceived they have good oral health status with 68% satisfied with their current oral health status. There was no significant association between their actual oral health status and their perceived satisfaction. However, increasing age, Malay and those eating dependently were less likely to satisfy with their oral health status. Meanwhile, those who were dependent on the staff to brush their teeth were more likely satisfied with their oral health status. Conclusion: There was a wide discrepancy between the actual and self-perceived oral health status among residents in care homes. Hence, it is crucial to improving awareness and knowledge among them in order to improve their oral health. Factors contributed to their oral health satisfaction should be acknowledged by all dental practitioners.